La frontière entre le bilād al-islām et le bilād al-Nūba : enjeux et ambiguïtés d’une frontière immobile (VIIe-XIIe siècle) - Robin Seignobos (Afriques)
Bilād al-Nūbaholds a special place in the Arab-Islamic juridical and ideological nomenclature. As a consequence of the failure to conquer Nubia in the 7th century, a peace treaty was signed that singled out this territory. These specificities were not devoid of consequences on the perception of the frontier between Islamic countries and Nubia. When delimiting bilād al-islām, Arabic geographers unanimously agreed in designating Aswan as the last frontier-town of Islam, in charge of defending Egyptian territory from potential Nubian enemies.A closer examination of the sources brings to light the unexpected complexity of this frontier system. It was apparently shaped around a geographical feature — the first cataract — which, far from being the impassable barrier described by some authors, was a place of transition between the two worlds. Taking advantage of this porous boundary, Islam gradually extended its influence far beyond Egypt’s southern bounds without substantially reworking the borderline.